A prenatally diagnosed gastric duplication cyst connecting the pancreatic duct and paraspinal region - Ozcakir, Esra; Sancar, Serpil; Yalcin, Omer; Kaya, Mete (The European Research Journal, 2017)
The gastrointestinal duplication of stomach is uncommon congenital anomalies of gastrointestinal tract. Herein a rare case of gastric duplication with newborn is being reported. A 14-day-old term female baby was admitted to our clinic with intermittent bilious vomiting and abdominal distention. In evaluation, abdominal cystic mass was detected in the left upper quadrant. The cyst which was attached to both the pancreatic duct and spinal cord was removed totally by laparotomy. A histologic examination showed gastric duplication cyst. The postoperative course was uneventful. There were no any complications at the 8-month follow-up period. This rare entity should be included in the differential diagnosis of cystic masses of the gastrointestinal tract and treated surgically by complete resection due to the risk of malignant transformation and other complications. This is the first case report that the gastric duplication cyst has a connection with both the pancreatic duct and spinal cord.